2023
DOI: 10.3390/molecules28020624
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Cocktail Formulation for Xylan Hydrolysis into Xylose and Xylooligosaccharides

Abstract: In the context of a biorefinery, lignocellulosic materials represent an important source of raw material for the bioconversion of cellulose, hemicellulose, and lignin into value-added products, such as xylose for fermentation, oligosaccharides, and bioplastics for packaging. Among the most abundant lignocellulosic materials in Brazil, sugarcane bagasse biomass stands out, as it is rich in cellulose and hemicellulose. In this context, through an experimental design, this study developed a robust enzyme cocktail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…It is possible that the effect of fib-CNF on intestinal bacteria led to weight loss. Numerous studies and review articles discuss the degradation of cellulose and other dietary fibers by intestinal bacteria [24][25][26][27][28][29][30][31][32][33][34]. Although cellulose is a central component of plant fiber and is abundant in diets with plant-derived foods, humans, like other mammals, rely on gut microbiota to break down cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the effect of fib-CNF on intestinal bacteria led to weight loss. Numerous studies and review articles discuss the degradation of cellulose and other dietary fibers by intestinal bacteria [24][25][26][27][28][29][30][31][32][33][34]. Although cellulose is a central component of plant fiber and is abundant in diets with plant-derived foods, humans, like other mammals, rely on gut microbiota to break down cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…The described structure of xylan determines the complexity of its complete enzymatic hydrolysis; therefore, for this purpose, the complex action of various enzymes is often used. α-L-arabinofuranosidases, α-D-glucuronidases, acetylxylanesterases, ferulic acid esterases and p-coumaric acid esterases act on various substituents of the branched xylan molecule, thereby increasing the availability of the xylose backbone for the action of xylanases [24,25,26]. It was shown that the yield of XOS during the combined destruction of lignocellulosic biomass by xylanase and arabinofuranosidase was 95.03% versus 30% when using single enzymes [9].…”
Section: Enzymatic Hydrolysis Of Xylanmentioning
confidence: 99%